Low Agreement Between Initial and Revised European Consensus on Definition and Diagnosis of Sarcopenia Applied to People Living With HIV - Oliveira, Vitor H. F.; Borsari, Ana L.; Cardenas, Jose David G.; Alves Junior, Claudio M.; Castro, Noemy F.; Marinello, Poliana C.; Padilha, Camila S. [UNESP]; Webel, Allison R.; Erlandson, Kristine M.; Deminice, Rafael (Lippincott Williams & Wilkins, 2021)
Background: In 2019, the European Working Group on Sarcopenia in Older People (EWGSOP2) proposed low muscle strength as the primary outcome for sarcopenia diagnosis instead of low muscle mass, as proposed in 2010 (EWGSOP1). Therefore, the aim of this study was to compare the prevalence of sarcopenia using both EWGSOP1 and EWGSOP2 operational definitions in people living with HIV (PLHIV) and to determine the agreement and correlation between different tests proposed by EWGSOP2. Setting: Cross-sectional study, where 302 PLHIV (151 men), 51.7 +/- 9.0 years old were evaluated for the presence of sarcopenia using both EWGSOP1 and EWGSOP2 operational definitions. Methods: Appendicular skeletal muscle was estimated using bioimpedance analysis. Handgrip strength, chair stand, gait speed, and static balance were used as muscle function measures. Agreement was determined using Cohen kappa and Pearson correlation coefficient was calculated. Results: Sarcopenia prevalence was 4.3% using EWGSOP1 and 1.0% using EWGSOP2. Agreement for sarcopenia diagnosis between EWGSOP1 and EWGSOP2 was fair (k = 0.37, P < 0.01). From the 13 cases of sarcopenia diagnosed using EWGSOP1, only 3 cases (23.1%) were also diagnosed using EWGSOP2. A medium correlation (r = -0.32, P < 0.01) and poor agreement (k = 0.14, P < 0.01) between muscle strength tests (handgrip strength and chair stand) were observed. Concordance between handgrip and chair stand was observed in 11 participants only, whereas 65 participants were considered to have low muscle strength using chair stand but not using handgrip. Conclusions: Lower sarcopenia prevalence using EWGSOP2 and low agreement between EWGSOP1 and EWGSOP2 operational definitions in diagnosing sarcopenia were observed in PLHIV.
Keywords: muscle function; physical examination; muscle strength dynamometer; muscle weakness; neuromuscular disease; body composition